Developing English Materials for Front Office of the XII Grade Students of SMK N 2 Singaraja - Ni Komang Sri Mariati; Nyoman Karina Wedhanti; Kadek Sintya Dewi (Language and Education Journal Undiksha, 2021)
The learning process is influenced by various factors. One of the important factors is the learning media as a supporter of the learning process, especially in learning ESP subjects. This study aimed to developed English materials for Front Office based on student’s need analyses. The subjects of this research were one teacher at SMK Negeri 2 Singaraja as the head of the front office at the school, 35 students in the second semester in class 12 AP2 of SMK Negeri 2 Singaraja, and one of the front office staff who worked at Kutabex Hotel. A questionnaire and a checklist used as the instrument to obtaining the data in this study. The method of this research used the Design and Development (D&D) model. The data has been analyzed with descriptive qualitative research. The result shows that the findings are (1) the study was developed three topics, namely: handling group guest check-in, handling group guest check out, and financial transaction based on the student’s need. (2) The design of English materials contains input, content focus, language focus, and task. In the task, the design included four English basic skills, namely: listening, speaking, reading, and writing. (3) The quality of the product belongs to very good quality based on the result of two expert judges.